Association of C-Reactive Protein With Cardiovascular Disease Mortality According to Diabetes Status: Pooled analyses of 25,979 participants from four U.K. prospective cohort studies - Kengne, Andre Pascal (American Diabetes Association, 2012)
OBJECTIVE: C-reactive protein (CRP) is associated with the risk of cardiovascular disease (CVD); whether the effects are modified by diabetes status still is unclear. This study investigated these issues and assessed the added value of CRP to predictions. RESEARCH DESIGN AND METHODS: Participants were drawn from representative samples of adults living in England and Scotland. Cox proportional hazards regression models were used to relate baseline plasma CRP with all-cause and CVD mortality during follow-up in men and women with and without diabetes. The added value of CRP to the predictions was assessed through c-statistic comparison and relative integrated discrimination improvement. RESULTS: A total of 25,979 participants (4.9% with diabetes) were followed for a median of 93 months, during which period there were 2,767 deaths (957 from CVD). CRP (per SD log(e)) was associated with a 53% (95% CI 43–64) and 43% (38–49) higher risk of cardiovascular and all-cause mortality, respectively. These associations were log linear and did not differ according to diabetes status (both P ≥ 0.08 for interaction), sex, and other risk factors. Adding CRP to conventional risk factors improved predictions overall and separately by diabetes status but not for CVD mortality, although such improvements only were marginal based on several discrimination statistics. CONCLUSIONS: The association between CRP and CVD was similar across diabetes status, and the effects are broadly similar across levels of other conventional risk factors.